Analysis of GNSS radio occultation data from satellite ZH‐01. Issue 6 (10th December 2018) - Cheng, Yan; Lin, Jian; Shen, XuHui; Wan, Xiang; Li, XinXing; Wang, WenJun
Abstract : The electromagnetic satellite Zhangheng 01 (ZH‐01) was successfully launched on February 2, 2018. The GNSS Radio Occultation (GRO) receiver on board the satellite is able to observe the occultation events of GPS and BeiDou navigation satellites. We analyzed the data acquired during the in‐orbit testing period. We concludes that the GRO ionosphere inversion results are reasonable, the trend is correct, the satellite can observe about 600 ionosphere occultation events each day. The global coverage of more than 30000 consecutive GRO events in more than two months were analyzed and compared with COSMIC observations: both the GRO and COSMIC occultation can realize global coverage: the N m F2 and H m F2 global distributions are similar and change obviously with latitude. We used three digisondes at different latitudes to analyze and compare the spatio‐temporally consistent GRO data: the RMSE of GRO N m F2 relative to digisonde is better than 9.41%, the correlation coefficient is better than 0.8682: the relative RMSE of H m F2 is better than 7.80% and the correlation coefficient is better than 0.7066.